Caractérisation de la morphologie des massifs dunaires de la région Pays de la Loire (France) face au risque de submersion marine - Martin Juigner; Marc Robin (VertigO, 2018)
Especially in areas with high human and non-human stakes, coastal dunes may act as natural forms of coastal protection against coastal flooding. This justifies the importance of assessing their ability at protecting the low-lying areas. This paper aims to propose a GIS-based reproducible method to assess : (i) the sensitivity of coastal dunes (ii) the exposure of non-human stakes to coastal floods (iii) the role of protection of coastal dunes. The segmentation along the 140 km of barrier systems and sand spits of the Pays de la Loire Region is carried out within 25*400 m boxes. Eight indicators are extracted from a generic dataset, then computed within each box : minimum dune crest height, dune base and dune volume of the frontal dune ; historical shoreline change ; extend of the low-lying areas and back dune base ; extend and potential water depth of the stakes. The aggregation of these indicators conducts to the indexes creation. The index value depends on the intensity and the concomitance of the indicators. This process, easy to implement, exhaustive and reproducible, allows : (i) to produce a fine diagnosis of the whole of study sites and (ii) to locate territories critically exposed to coastal flooding. This methodology is intended to guide and prioritize the public action towards the at-risk areas through the diffusion of an objective knowledge of the risk.